Possible contributors to students’ non-completion of the postgraduate nursing diploma at Stellenbosch University - Essa, Ilhaam (Stellenbosch : University of Stellenbosch, 2010)
Research report (MPhil (Curriculum Studies))--University of Stellenbosch, 2010.